Three-atomic clusters of rare gases within Faddeev approach - Korobitsin, A. A.; Kolganova, E. A.; Klimenko, O. P.; Sandhas, W. (Physics of atomic nuclei, 2017)
The properties of the rare gas clusters of helium and neon are studied. The calculations of the bound state energies of helium and neon trimers are performed within Faddeev differential equation in total angular momentum representation.